Evaluating customer retention strategies at Garden City Savings and Loans Limited - Nti, Philip (2014)
A thesis submitted to the Department of Marketing and Corporate Strategy, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration, August-2009